Salivary Cortisol Increases After Bariatric Surgery in Women - Valentine, A.R.; Raff, H.; Liu, H.; Ballesteros, M.; Rose, J.M.; Jossart, G.H.; Cirangle, P.; Bravata, D.M. (Hormone and Metabolic Research, 2011)
Cortisol increases have been associated with psychological and physiological stress; however, cortisol dynamics after weight loss (bariatric) surgery have not been defined. Obese participants not using exogenous glucocorticoids were eligible to participate. Female participants (n=24) provided salivary cortisol samples at bedtime, upon awakening the following morning, and 30 min after awakening before, and at 6 or 12 months after bariatric surgery. The Medical Outcomes Study Short Form-12 version 2 questionnaire regarding health-related quality of life was also completed. Preoperatively, mean body mass index was 45.1±8.1 kg/m2. Mean late night (1.8±1.1 nmol/l), awakening (10.7±7.4 nmol/l), and after-awakening (11.5±7.9 nmol/l) salivary cortisol values were within normal ranges. The cortisol awakening response (mean 21.1±79.7%, median 13.7%) was at the low end of normal. Preoperatively, participants had lower mental and physical health-related quality of life scores than US adult norms (p<0.001). Salivary cortisol was not correlated with measures of health-related quality of life. Mean BMI decreased over time (p<0.001) and participants experienced improved physical and mental health-related quality of life (p≤0.011). Postoperative late night salivary cortisol was not different from preoperative values. Awakening and after-awakening cortisol levels were higher than preoperative values (15.3±7.7 nmol/l, p=0.013; 17.5±10.2 nmol/l, p=0.005; respectively), but the cortisol awakening response was not changed (mean 26.7±66.2%; median 7.8%). Morning salivary cortisol increased at long-term follow-up after bariatric surgery. Although self-evaluated mental and physical health improved after surgery, the cortisol awakening response is at the low end of normal, which may indicate continued physiological stress.